Onset of labour epidural analgesia with low‐dose bupivacaine and different doses of fentanyl1. (19th October 2017) - Vedagiri Sai, R.; Singh, S. I.; Qasem, F.; Nguyen, D.; Dhir, S.; Marmai, K.; Adam, R.; Jones, P. M.
Summary: This study investigated the effects of different doses of epidural fentanyl on the time to onset of epidural analgesia in women in early labour. We hypothesised that onset of epidural labour analgesia (the primary outcome defined as time in minutes from completion of epidural bolus to the first uterine contraction with a numeric pain rating scale [NPRS] score ≤ 3) would be faster with 100 μg of fentanyl epidural bolus compared with 20 μg or 50 μg. Epidural labour analgesia was initiated with 20 μg of fentanyl (F20 group), 50 μg (F50 group) or 100 μg (F100 group) along with 10 ml bupivacaine 0.08% as the loading dose. We randomly allocated 105 patients, with 35 patients in each group. Median (IQR [range]) time to achieve NPRS ≤ 3 was 18 (11–30 [6–20]) min in F20, 10 (8–19 [4–30]) min in F50 and 10 (6–16 [3–30]) min in F100 groups. There was a significant difference in onset times comparing F100 with F20 (p < 0.001) and F50 with F20 (p = 0.007), but not significantly different comparing F100 with F50 (p = 0.19). The median (IQR [range]) time from the epidural loading dose to first patient controlled epidural analgesia bolus was 61 min (20–165 [20–420]) in F20, 118 min (66–176 [20–396]) in F50 and 150 min (66–214 [30‐764]) in F100 groups. This was not statistically significant (p = 0.16) comparing the F20 with the F100 group. There were no significant differences in maternal side‐effects, mode of delivery, patient satisfaction scores or neonatal Apgar scores between all groups. We conclude that the 50 μg and 100 μg fentanyl doses were associated with reduced onset times to effective analgesia compared with the 20 μg dose.